2021
DOI: 10.25077/jif.14.1.10-20.2022
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Comparison of IMERG Precipitation Products with Optical Rain Gauge Observations over Kototabang, Indonesia

Abstract: Satellite-based precipitation estimates play a crucial role in many hydrological and numerical weather models, especially to overcome the scarcity of rain gauge data. Globally gridded rainfall product from Integrated Multi-Satellite Retrievals for Global Precipitation Measurement (GPM) (IMERG) has been used in a wide range of hydrological applications. However, the IMERG is inherently prone to errors and biases. This study evaluated the performance of the IMERG-Final run (IMERG-F) product to estimate rainfall … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 29 publications
2
2
0
Order By: Relevance
“…The station ID (located above sea level) as shown in Figure 2 were 96071 (328 m above sea level/ASL), 96581 (2 m ASL), 150010 (43 m ASL), and 150146 (184 m ASL). Rain gauge (AWS and MRG) and IMERG captured hourly and daily precipitation temporal trend, which is consistent with a previous study in West Sumatra [42].…”
Section: Gpm Imerg Precipitation Productssupporting
confidence: 91%
See 3 more Smart Citations
“…The station ID (located above sea level) as shown in Figure 2 were 96071 (328 m above sea level/ASL), 96581 (2 m ASL), 150010 (43 m ASL), and 150146 (184 m ASL). Rain gauge (AWS and MRG) and IMERG captured hourly and daily precipitation temporal trend, which is consistent with a previous study in West Sumatra [42].…”
Section: Gpm Imerg Precipitation Productssupporting
confidence: 91%
“…Although most stations showed that IMERG overestimated rainfall, 35.4% of MRG and 41.8% of AWS stations showed that IMERG underestimated it. The dominance of the overestimated value from the observations of hourly rainfall found in this study was consistent with the pattern of overestimation often found from IMERG observations [15,42,67,68]. From all continuous statistical quantities, it can be seen that the accuracy of hourly rainfall observations from IMERG at IMC still needs to be improved.…”
Section: Hourly Assessmentsupporting
confidence: 89%
See 2 more Smart Citations
“…Multiple studies conducted in Indonesia have focused on validating satellite precipitation products for rainfall predictions [34], [40], [41], Pratiwi et al [42] conducted research where they evaluated TRMM 3B42, TRMM 3B42RT, GPM, and PERSIANN CCS satellite data. The study revealed that the GPM satellite provided good results for predicting observed rainfall data in the Dengkeng watershed, specifically for the daily period, with a correlation coefficient of 0.66.…”
Section: Introductionmentioning
confidence: 99%